Família, obesidade, cirurgia bariátrica e suas interfaces - Colombo, Priscila Brito (2015)
The general objective of this research was to understand the meaning attributed to obesity and weight loss induced by bariatric surgery in families with more than one operated member. The specific objectives were: to investigate events that have contributed to the history of weight gain; to relate obesity to the family rituals and habits, besides identifying actions and motivations to choose bariatric surgery as an alternative treatment against obesity. The methodology was qualitative. The primary data were initially collected by applying an open interview guide with a trigger question allowing respondents to answer freely. In order to obtain additional information, it was used a survey with socio-demographic and disease data. For this study, it was used sociologic approaches and systems theory aiming to substantiate the analysis and understanding of the data. Relevant results confirm that the operation provides an opportunity to re-build the identity of the person. However, it was realized that the surgery does not provide an extensive change for the entire family, some of them temporarily reorganize themselves to welcome the operated limb but it was not observed changes of patterns, habits and rituals. Thus it is concluded that the change happens at the individual level and, by reflecting the trajectory of the subject "ex-obese" who chose gastroplasty to treat their disease, it is possible to progress in discussions, research and strategies that validate the subjective universe of these people as well as provide resources to become active subjects of own life